Functional properties, antioxidant activities and storage stability of cookies from germinated brown rice and rice-potato starch composite flour - Bolarinwa, Islamiyat Folashade; Syed Muhammad, Sharifah Kharidah (Universiti Putra Malaysia Press, 2019)
Cookies are convenient food for people of all ages. Consumers' interest for gluten free cookies is increasing recently due to awareness on gluten allergy. This study evaluated the functional properties and antioxidant activities of germinated brown rice flour (GBRF) and non-germinated brown rice flour (NGBRF), and GBRF-potato starch blend (3:1), and NGBRF-potato starch blend (3:1). Storage stability and sensory acceptance of cookies produced from the various flour samples were also evaluated. The flours had significantly different values in most of the functional properties. However, the Housner's ratio (1.18- 1.35), Carr index (14.94-25.67) and water absorption index (1.88-2.14 g/g) of the flours were not significantly different. GBRF and germinated brown rice flour cookies (GBRFC) had the highest antioxidant activities with DPPH values of 40.61 µM TE/g and 37.67 µM TE/g, respectively, and FRAP values of 39.84 µM TE/g and 38.29 µM TE/g, respectively. The GBRFC had higher total phenolic content (152.30 mg GAE/100g) than cookies from GBRF-starch blend (107.37 mg GAE/100 g). Sensory evaluation results showed that all the cookies were similarly rated for aroma, texture, mouth feel, crispiness and overall acceptance. However, cookies prepared from wheat flour, and germinated brown rice-potato starch (GBRPS) had the highest sensory scores for overall acceptance. The hardness of cookies produced from GBRPS was similar to that of the freshly produced cookies after 7 days of storage at room temperature.